ANALISIS STRATEGI PEMASARAN TERHADAP PENINGKATAN PENJUALAN: STUDI KASUS PADA UMKM TOKO NURHIDAYAH DI KABUPATEN MAJENE, SULAWESI BARAT - Artika, Artika; Putra, Feby Arma (LP2M Universitas Bina Bangsa, 2024)
The focus of this research is how marketing strategy influences increasing sales at TOKO Nurhidayah MSMEs. Qualitative research methods using interview and documentation techniques for business owners and employees were used in this research to analyze the impact of marketing strategies on increasing sales at Nurhidayah SHOP MSMEs, Majene Regency. The research results show that segmentation, targeting, positioning and marketing mix are part of strategic management. Based on the research results above, it can be concluded: Currently, analysis of the best marketing techniques to increase sales focuses on segmentation, targeting, positioning and marketing components